Type 3 Diplococcus Pneumonia in Laboratory Rats - Baer, H. (1969)
An acute respiratory disease, due to Diplococcus pneumoniae type 3, affecting Wistar and Sprague-Dawley rats is described. The infection was experimentally transmitted to Sprague-Dawley rats. The zoonotic potential of the condition dictated euthanasia of affected animals and instigation of rigid sanitary measures.